Inclusive and Enjoyable Physical Activity for Older Adults: The JOIN4JOY Project (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Older adults remain the least physically active group in Europe, with barriers such as low socioeconomic status, health limitations, and social exclusion contributing to inactivity. JOIN4JOY aims to reduce sedentary behaviour (SB) and increase physical activity (PA) among adults aged 65+, living in community and nursing homes. This project innovatively integrates co-creation, gamification, and social inclusion perspective to design PA programme focused on enjoyment – a key to sustained engagement. By emphasising intergenerational collaboration, inclusive practice, and virtual communities of practice (VCoPs), JOIN4JOY presents a novel model that promotes healthy ageing.Project Description: Development. The JOIN4JOY intervention programme was co-developed through a participatory approach involving older adults (end-users), family members, professionals, students, and policymakers across five European countries: Denmark, France, Germany, Italy, and Spain. Focus groups were guided by the Octalysis gamification framework to ensure enjoyment and engagement were considered. Training modules and materials were developed collaboratively, integrating students and evidence-based strategies from prior successful interventions.Implementation. The project co-created and implemented two tailored programmes: JOIN4JOY-C (for community-dwelling older adults) and JOIN4JOY-NH (for the residents of nursing homes). Both programmes were piloted (Pilot 1 and Pilot 2) by trained professionals and students, combining group PA sessions, self-management strategies, and social engagement.Evaluation. A mixed-method evaluation was used to assess feasibility, acceptability, and impact of the programme. Quantitative tools included subjective questionnaires and scales as well as accelerometries for objective measurement of PA and SB. Qualitative interviews with participants and trainers explored their experiences and perceived benefits of the programme.Dissemination and Scale-Up. The open-access training platform linked to VCoPs was established nationally in local languages and internationally in English to enable peer learning and practitioner support as well as the scale-up of the project. Public events, publications, and practitioner networks will support its dissemination across Europe.Conclusion: JOIN4JOY shows how co-creation, gamification, and inclusive design can reshape PA programmes for older adults, shifting the focus towards enjoyment and social inclusion. Preliminary results indicate high levels of satisfaction and enjoyment among participants. The project offers valuable insights for advancing long-term, inclusive approaches to promote PA among older adults.